Pengujian Website Penerimaan Peserta Didik Baru SMK Bina Mandiri Al Qodiriyah Dengan Black Box Teknik Equivalence Partitioning - Wahid, Mohamad Fathur Rohman; Hidayat, Alfin; Suardinata, I Wayan (Jurnal Informatika dan Komputer, 2025)
The development of information and communication technology (ICT) has had a significant impact on various sectors of life, including education. This research aims to develop an online New Student Admission System (PPDB) for SMK Bina Mandiri Al Qodiriyah in Banyuwangi, East Java, which currently operates with a manual registration system. To enhance the efficiency and accuracy of the registration process, Human-Centered Design (HCD) methodology is employed in the website design. Additionally, Black Box Testing using Equivalence Partitioning technique is applied to ensure the quality of the software. The test results indicate that this approach is effective in categorizing input data and reducing system errors, while ensuring all features operate smoothly. The resulting website design is also optimized to enhance user experience, demonstrating the potential of this technology to improve efficiency, accessibility, and data accuracy in the new student admission process.